REORIENTASI DAN REKONSTRUKSI PARADIGMA LAMA PENDIDIKAN KEWARGANEGARAAN MENUJU INDONESIA BARD - Cholisin, Cholisin (Jurnal Cakrawala Pendidikan, 2016)
The paradigm of last ivic education was heavi ly orientated to the development of moral values which diet not have a clear knowledge basis, aand intended to support the New Order regime (status quo). The po itical changes from otoritariannisme to democracy int ndeed to establish ciil society into the crisis ofthe exsistnce ofthe civic education. The new paradigm of the civic education is n eded to over come the crisis. The aradigm iss buit in·· accord call with the New Indonesian and construted through the antithesis of the old one. The new paradigm isexpected to have criterion as follow: first, it is an strongly orianted knowledge. It means the themes all knowlwdge such as politicals, law. econonlic and the others of social sciences were developed with specils emphasize on participatory approach of the social ’’"scienses (enlahcip"ation of the social scieces), however it should have orientation to the students. Second, it is strongly orientated to the empowerment of th citizen. Consequentl we needed to reveal the orientation of the citizenship, and the development of civic culture and to develop the criticissm attitudes and the cretive citizen. The above mentioned new paradigm’ of civic education will be able to suppart the development of civil society asa a New indonesian society, and will not risk to the changes ofthe regime